„Külföldtudományok” a berlini egyetemen a II. világháború idején = “Foreign studies” at the university of Berlin during WWII - Orosz, László (Közép-Európai Közlemények, 2018)
Providing intellectual support for National Socialist Germany’s expansive foreign policy goals was among the priorities of German academic and intellectual life of that period. Institutions were set up with the goal of undertaking hard research or some more easily understood mixture thereof (mainly of ideological persuasion) and disseminating the findings to a wider audience or, in other words, advancing the development of a new-thinking intellectual elite. With the war ongoing, there soon arose a political need for a full-range of studies related to “foreignness”, which would provide scientific cover for any potential political pursuits, namely from the most trustworthy of German scientists, and of course within close proximity to the Reich’s leadership, which is to say, in the capital of the Reich. For this reason the University of Berlin created a so-called Faculty of Foreign Studies, which this summary wishes to analyze, in addition to the related academic institute’s operation, institutional background, organizational arrangement and ultimately the academic concept as it related to the states of the East and Southeastern European region.